DUKUNGAN PEROKOK DAN BUKAN PEROKOK TERHADAP KEBIJAKAN PENGENDALIAN TEMBAKAU DI KOTA DENPASAR DAN YOGYAKARTA - Mardhiati, Retno; Fatimah, Nisma; Andayani, Novi (ARKESMAS [Arsip Kesehatan Masyarakat], 2016)
Introduction. The Framework Convention on Tobacco Control (FCTC), which was initiated by WHO isthe initial movement of protection for people who do not smoke. Support for tobacco control policies inBali and Yogyakarta is given not only by the people of nonsmokers but also by the people who have thesmoking behavior.Methods. This study was a survey poll with sample of 128 respondents from Denpasar and Yogyakarta.Respondents were selected using cluster sampling technique. Data collected by interviewing respondentsaged 15-50 years. The instrument of collecting data was questionnaire. Data collection was conductedfrom May to June 2013. The analysis used comparative of the proportion of smokers and non-smokerssupport for tobacco control policies.Result.: Characteristics of respondents in Denpasar, most of them were not smoking (57.5%) while mostof respondents in the city of Yogyakarta were smoking (54.2%). The comparison in Denpasar showedsupport from smokers (97.1%) and non-smokers (97.8%) were same in supporting the implementation ofthe ban on smoking in public places and bounded workspace. The ban of smoking in public transport andshopping malls were more supported by non-smokers (97.8%) than smokers (79.4%). In Yogyakarta, nonsmokers support the implementation of legislation to ban smoking in public places and boundedworkspace (100%), at shopping centers and public transportation (95.5%). Than smokers in Denpasarand Yogyakarta are provide supporting respectively, 94.1% and 84.6% supporting regulation pictorialwarnings on all tobacco product packaging, 85.3% and 88.5% supporting regulation for warning thedangers of smoking on the outer packaging of cigarettes, 79.4% and 72% support a ban regulationscoloring, logos on cigarette packs, only 44.1% and 53.8% supported a ban on using labels flavors suchas menthol, chocolate and coffee flavor.Conclusions. Support for smoking control regulations given by smoker or non-smoker respondents inDenpasar and Yogyakarta. There should be a continuous effort by planned and provide health educationabout dangers of smoking and exposure of cigarette smoke in all society.